2015
DOI: 10.1039/c5cp01922b
|View full text |Cite
|
Sign up to set email alerts
|

Single Pt atom stabilized on nitrogen doped graphene: CO oxidation readily occurs via the tri-molecular Eley–Rideal mechanism

Abstract: Single-atom catalysts, especially with single Pt atoms, have attracted more and more attention due to their high catalytic activity for CO oxidation. The outstanding stability and catalytic activity of a single Pt atom supported on nitrogen doped graphene (Pt/NG) are revealed using first-principles calculations. We find that the stability of a Pt atom on the NG can be promoted by picking an appropriate doping configuration. The exceptionally stable Pt/NG catalyst exhibits excellent catalytic activity for CO ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(40 citation statements)
references
References 58 publications
3
36
0
1
Order By: Relevance
“…In addition, firstprinciples calculations showed that N-doping can introduce localized defect states in the vicinity of the Fermi level of pristine graphene and that the calculated diffusion barrier of Pt atoms on N-doped graphene (2.97 eV) was much higher than that on pristine graphene (~ 0.14 eV),effectively stabilizing deposited Pt atoms [192]. Furthermore, N-doping configurations in graphene substrates were found to be able to affect the stability of Pt atoms on NG and that Pt-NG support interactions can be stronger than Pt-Pt interactions by picking appropriate doping configurations [193]. Recent calculations also indicated that single Co atoms embedded into pyridinic vacancy sites of nitrogen-doped graphene were more stable than that of Pt [194] as confirmed by experimental observations that showed that these bonded Co atoms by N atoms were stable and can function as highly active HER catalysts in both acid and base media [111].…”
Section: Carbon-based Materialsmentioning
confidence: 95%
“…In addition, firstprinciples calculations showed that N-doping can introduce localized defect states in the vicinity of the Fermi level of pristine graphene and that the calculated diffusion barrier of Pt atoms on N-doped graphene (2.97 eV) was much higher than that on pristine graphene (~ 0.14 eV),effectively stabilizing deposited Pt atoms [192]. Furthermore, N-doping configurations in graphene substrates were found to be able to affect the stability of Pt atoms on NG and that Pt-NG support interactions can be stronger than Pt-Pt interactions by picking appropriate doping configurations [193]. Recent calculations also indicated that single Co atoms embedded into pyridinic vacancy sites of nitrogen-doped graphene were more stable than that of Pt [194] as confirmed by experimental observations that showed that these bonded Co atoms by N atoms were stable and can function as highly active HER catalysts in both acid and base media [111].…”
Section: Carbon-based Materialsmentioning
confidence: 95%
“…0.14 eV). These results suggested that sintering and aggregation of deposited single Pt atoms (in PtN 3 form) would be inhibited under conventional reaction conditions.The high catalytic activity of the PtN 3 centers was attributed to beneficial interfacial Pt-N interactions,w hich may facilitate the activation of O 2 .Different from the catalyst model that Meng and co-workers employed, Lu, Yang et al [47] selected ag raphene material with four Catoms replaced by Natoms as the support (Tet-NG) for Pt single-atom catalysts. They showed that the diffusion barrier ( Figure 3) of Pt on Te t-NG was 1.65 eV,w hich was 0.26 eV higher than that on Tr i-NG (graphene with three Catoms replaced by Natoms).…”
Section: Textural Properties and Characterization Of Metal Nps Suppormentioning
confidence: 99%
“…For instance, while Pd 1 /TiO 2 and Pt 1 /SiO 2 showed no activity in catalytic CO oxidation even at elevated temperature [21,22], Pd 1 /La-Al 2 O 3 and Pt 1 /FeO x exhibited high activities [6,23]. It is vital to understand at the molecular level how supports are involved in catalysis [22,[24][25][26][27][28]. However, the atomic-resolution characterization of interfacial species surrounding isolated metal atoms remains a grand challenge [29][30][31][32][33], preventing us from addressing the key question of how supports are involved in the catalysis of atomically dispersed metal catalysts.…”
Section: Introductionmentioning
confidence: 99%